Procreation and parenthood the ethics of bearing and rearing children - Archard, David; Benatar, David (Oxford : Clarendon, 2010)
Producing and rearing children are immensely important human activities. This collection offers new and original essays by leading philosophers on some of the main ethical issues raised by these activities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Life; Parenting -- Moral and ethical aspects